Pengaruh Keikutsertaan Les Privat terhadap Kemampuan Membaca Anak Didik Kelas TK B di TK At - Tazkiyah Kebomas Gresik - Desy Anggraeni (Tadrisuna : Jurnal Pendidikan Islam dan Kajian Keislaman, 2024)
This research employs a quantitative approach using a correlational method. The subjects of this study are TK B students and teachers at At-Tazkiyah Kindergarten, Kebomas, Gresik, during the 2023–2024 academic year. Data were collected through tests, observation, and documentation. Based on the results of the research and data analysis conducted at At-Tazkiyah Kindergarten, Kebomas, Gresik, the calculation of the contingency correlation coefficient yielded a value of 0.386. This value was then compared with the significance level of 5% for N = 28 and degrees of freedom (df) = N − 2 = 26, which produced a critical value of 0.374. Since 0.386 ≥ 0.374, it can be concluded that participation in private tutoring has a significant effect on reading ability; therefore, the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted. Furthermore, based on the interpretation guidelines for correlation coefficients, the effect of participation in private tutoring is categorized as low